Geoelectrical survey over perched aquifers in the northern part of Upper Sakarya River Basin, Türkiye - Ertekin Can; Ulugergerli Emin U (Journal of Groundwater Science and Engineering, 2022)
In this study, a groundwater exploration survey was conducted using the DC Resistivity (DCR) method in a hydrogeological setting containing a perched aquifer. DCR data were gathered and an electrical tomography section was recovered using conventional four-electrode instruments with a Schlumberger array and a two-dimensional (2D) inversion scheme. The proposed scheme was tested over a synthetic three-dimensional (3D) subsurface model before deploying it in a field situation. The proposed method indicated that gathering data with simple four-electrode instruments at stations along a line and 2D inversion of datasets at multiple stations can recover depth intervals of the studied aquifer in the hydrogeological setting even if it has a 3D structure. In this study, 2D inversion of parallel profiles formed a pseudo-3D volume of the subsurface resistivity structures and mapped out multiple resistive (>25 ohm·m) bodies at shallow (between 50–100 m) and deep sections (>150 m). In general, the proposed method is convenient to encounter geological units that have limited vertical and spatial extensions in any direction and presents resistivity contrast from groundwater-bearing geologic materials.